Rainwater Harvesting for Managed Aquifer Recharge (MAR)—A Case Study from Urban Centre in Punjab Pakistan - Zakir-Hassan, Ghulam; Akhtar, Saleem; Punthakey, Jehangir F.; Afzal, Muhammad; Shabir, Ghulam; Hassan, Faiz Raza; Khan, Muhammad Ali Hassan (Journal of Hydrological Ecology and Water Security, 2025)
Rising trends in global population have resulted in increased urbanization, industrialization, and food demands. This has resulted in the rapidly increasing water demands for domestic, agricultural and industrial sectors; which have severely depleted groundwater resources in Pakistan. The urban centres like Lahore city—the capital of Punjab province and the 2nd largest city of Pakistan. To address this challenge, a field-scale Managed Aquifer Recharge (MAR) system integrated with Rainwater Harvesting (RWH) was developed and tested to evaluate its feasibility and efficiency for urban groundwater recovery. In this system, rainwater collected from paved surfaces was filtered and injected into a Pleistocene sand aquifer through recharge wells. Double filtration mechanism has been introduced in the model to ensure good quality rainwater is recharged into the aquifer. Field monitoring during multiple rainfall events demonstrated successful infiltration and aquifer-storage, with recharge volumes of 150,700, 281,097, and 89,887 L of rainwater corresponding to potential domestic water supplies for 132, 246, and 79 days for an average household respectively. The results confirm that decentralized RWH–MAR systems can significantly enhance aquifer replenishment in overexploited urban aquifers. The study underscores the viability of such systems for broader implementation in Punjab and other similar semi-arid regions, contributing to sustainable groundwater management and urban water resilience in Pakistan.